Postpartum fevers, a rare presentation of secondary hemophagocytic lymphohistiocytosis - Jacqueline Lee; Brian Pham; Zarir E. Karanjawala; Oyebimpe Adesina (Clinical Case Reports, 2023)
Abstract Hemophagocytic lymphohistiocytosis (HLH) is a rare disease of excessive immune system activation. We report a case of HLH in a 20‐year‐old primigravid woman who presented with postpartum fevers. She was successfully treated with dexamethasone and anakinra, a deviation from the HLH‐94 protocol, to preserve her ability to breastfeed.